Spatial Patterns of Canopy Disturbance and Shortleaf Pine in a Mixedwood Forest. Issue 4 (12th June 2021) - Goode, J Davis; Hart, Justin L; Dey, Daniel C; Torreano, Scott J; Clark, Stacy L
Abstract: The spatial structure of forest ecosystems is dominated by the horizontal and vertical distribution of trees and their attributes across space. Canopy disturbance is a primary regulator of forest spatial structure. Although the importance of tree spatial pattern is widely acknowledged as it affects important ecosystem processes such as regeneration and recruitment into the overstory, quantitative reference spatial conditions to inform silvicultural systems are lacking. This is especially true for mixedwood forests, defined as those that contain hardwoods and softwoods in the canopy. We used data from a preexisting network of plots in a complex-stage mixedwood stand to investigate the influence of canopy disturbance on stand and neighborhood-scale spatial patterns. We reconstructed canopy disturbance history and linked detected stand-wide and gap-scale disturbance events to establishment and spatial patterns of shortleaf pine. The majority of shortleaf pine establishment coincided with stand-wide or gap-scale disturbance. Shortleaf pine was clustered at the stand scale but was randomly distributed at the neighborhood scale (i.e. five tree clusters), which was a legacy of the historical disturbance regime. These results may be used to improve natural disturbance-based silvicultural systems to restore and maintain mixedwood forests for enhanced resilience and provisioning of ecosystem goods and services.